Analysis of Teacher Pedagogigal Competence In English Teaching Learning Process - Nadiya Agustiadie; Silviana Silviana (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
The aim of this research are to determine the pedagogical competence of teachers in teaching English at MTsN 5 Aceh Utara. The design of this research is descriptive qualitative. In finding the valid data about the Analysis of Teacher Pedagogic Competence in the English Teaching and Learning Process, the researchers used data collection techniques through observation, interviews and documentation. From the results of research in the preparation of the author's thesis on the Analysis of Teacher Pedagogic Competence in the English Teaching and Learning Process, the authors can conclude that: the pedagogic of the English teacher at MTS N 5 Aceh Utara is very good, in the process of learning and teaching English each teacher prepares lesson plans (RPP) first, make an annual program, every semester make a promissory note (semester program) and compile a syllabus. when the process of learning to teach English, the teacher uses the right method for each material to be delivered so that students do not feel bored, every teacher takes a direct approach to students who are lacking in learning English, even the teacher teaches English to students by spelling like learning read Indonesian, and students who do not understand will be imprisoned individually.